2018
DOI: 10.1002/bbb.1895
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in metabolic engineering of Corynebacterium glutamicum as a potential platform microorganism for biorefinery

Abstract: The fermentative production of platform chemicals in biorefineries is a sustainable alternative to current petroleum‐refining processes. Industrial microorganisms, such as Escherichia coli, Saccharomyces cerevisiae, and Corynebacterium glutamicum, have been engineered as microbial cell factories that are able to utilize biomass for the production of value‐added platform chemicals and polymers. Compared to E. coli and S. cerevisiae, C. glutamicum displays weak carbon catabolite repression and can co‐utilize mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 157 publications
(239 reference statements)
1
42
0
Order By: Relevance
“…While glucose is considered as one of the preferential glucose for C. glutamicum growth, it was also reported that C. glutamicum was able to grow on a variety of other sugars or organic acids as a single or combined carbon and/or energy source. It was, however, reported that C. glutamicum ATCC 13032 was not able to grow on C4‐dicarboxylates as succinate, fumarate, and malate, as sole carbon source .…”
Section: Discussionmentioning
confidence: 99%
“…While glucose is considered as one of the preferential glucose for C. glutamicum growth, it was also reported that C. glutamicum was able to grow on a variety of other sugars or organic acids as a single or combined carbon and/or energy source. It was, however, reported that C. glutamicum ATCC 13032 was not able to grow on C4‐dicarboxylates as succinate, fumarate, and malate, as sole carbon source .…”
Section: Discussionmentioning
confidence: 99%
“…Biorefinery processes have been developed to establish a sustainable alternative to produce chemicals, polymers, and fuels, and they currently rely on petroleum-based processes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Development of recombinant microorganisms capable of converting a broader range of renewable biomass feedstock into bio-based chemicals, with properties comparable to those of conventional petrochemical products, have been extensively studied [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, processes for the production of bio-polymers, such as polylactic acid (PLA) and polybutylene succinate (PBS) in a biorefinery have been established [21][22][23]. Polymerization of microbial fermentation derived-monomers, such as diamines, dicarboxylic acids, and amino carboxylic acids, yields these bio-based polymers [4,5]. Escherichia coli is one of the most commonly used microorganisms for the production of monomers used to prepare bio-based polymers [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations